FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN WUS DALAM PENGGUNAAN ALAT KONTRASEPSI IUD - Rasmina Anggi; Sarma Lumbanraja; Elvi Era Liesmayani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Health development is an investment in boosting human resource quality. In order to accomplish the desired health development, the family planning program is an excellent strategy to promote family resilience, health, and safety for mothers, children, and women. The IUD is a safe, effective, and low-risk contraception. The purpose of this study is to identify the variables related with women of reproductive age using IUD contraception. This study employed an analytic survey with a cross-sectional design. The population were 1,071 people, and the sample was 91 people taken by using incidental sampling. A questionnaire was employed as the measuring method, with univariate data analysis, bivariate with chi square, and multivariate testing.The results of this study were obtained from 91 respondents who used IUDs, 29 respondents (31.87%) and non-IUDs, 62 respondents (68.13%). Variable knowledge about side effects (p-value=0.000), experience of use (p-value=0.001), culture, traditions and beliefs (p-value=0.006), where to obtain family planning services (p-value=0.007) and support from health workers (p-value=0.000) has a relationship with the participation of women of childbearing age in the use of IUD contraception. The most significant variables in the use of IUD contraception included varying awareness about adverse effects, culture, customs, and beliefs, and support from health personnel. The variables that most affect the involvement of women of reproductive age in the use of IUD family planning are health worker support, culture, traditions, and beliefs, and understanding of adverse effects. It is recommended that health professionals assist in increasing the use of the IUD as an effective and efficient contraception